Novel three-dimensional nanostructured carbon materials as electrocatalyst support in low-temperature fuel cells - Elangovan, Ayyappan (Kansas State University, 2020)
Human sustainability and fossil fuel depletion are driving the demand for alternative energy sources. Low-temperature fuel cells (LTFCs) can be an alternative sustainable energy source owing to their high energy conversion efficiency, environmental friendliness, and ability to use renewable fuels. Despite the success, the high cost, poor durability, and susceptibility to fuel poison of the Pt-based electrocatalysts limit the widespread applications of LTFCs. Therefore, numerous efforts have been devoted to developing novel nanostructured carbon materials as electrocatalyst support to address the issues faced by the commercial Pt-based catalysts. This research focuses on a unique three-dimensional carbon support in this direction. In the first approach, a systematic study has been carried out on oxygen reduction reaction (ORR) with ion-beam sputtered Pt catalyst (at Pt loadings of 6.5 - 43 μg cm⁻²) on a vertically aligned carbon nanofiber (VACNF) array, consisting of conically stacked graphitic microstructures. Rotating disk electrode (RDE) studies reveal that thick 3D architecture of VACNFs exhibits enhanced limiting current density that deviates from the Levich equation for conventional thin-film catalysts. Nevertheless, useful information can be derived from RDE experiments with such systems. Molecular models representing VACNFs have been constructed to explore their capability as catalyst supports for ORR. Platinum atoms form strong bonds at the open graphitic edges in VACNFs, corroborating the role of VACNF in stabilizing Pt. Density Functional Theory (DFT) calculations further elucidate the two-electron and four-electron ORR pathways on the bare VACNF and Pt/VACNF catalysts, respectively. Furthermore, the Pt/VACNF catalysts show enhanced tolerance to methanol oxidation and a higher ability to recover from carbon monoxide poisoning in comparison to the benchmark Pt/C catalysts. Following the success of VACNFs for the ORR, in the second approach, the role of additional nitrogen doping into the three-dimensional VACNF array by NH₃ plasma annealing in improving the durability of the Pt catalysts towards the ORR has been explored. The additional nitrogen present in N-VACNF support enhances the metal-support interaction which helps in reducing the Pt particle size from 3.1 nm to 2.3 nm. Pt/N-VACNF catalyst shows better durability when compared to the Pt/VACNF and Pt/C with similar Pt loading. DFT calculations validate the increase in stability of the Pt NPs with an increase in pyridinic N and illustrate the molecular ORR pathway for Pt/N-VACNF. Moreover, the Pt/N-VACNF catalyst is also found to have an enhanced tolerance towards the methanol crossover. In the third approach, the role of three-dimensionally architectured in-situ N-doped VACNFs as a catalyst support for methanol oxidation reaction (MOR) has been studied in acidic and alkaline media. The abundant graphitic edge sites at the sidewall of N-doped VACNF strongly anchor the deposited platinum group metal (PGM) catalysts and induce a partial electron transfer between the PGM catalysts and support. DFT calculations reveal that the strong metal-support interaction substantially increases the adsorption energy of OH, particularly near the N-doping sites, which helps to compete and remove the adsorbed intermediate species generated during MOR. The PGM catalysts on N-doped VACNF support exhibit CO stripping at lower potentials comparing to the commercial Vulcan carbon support and present an enhanced electrocatalytic performance and better durability for MOR.
Keywords: Electrocatalysis; Oxygen reduction reaction; Methanol oxidation reaction; Three-dimensional carbon support; Vertically aligned carbon nanofibers; PGM electrocatalysts